ChemInform Abstract: A Trialkylphosphine‐Driven Chemical Transformation Route to Ag‐ and Bi‐Based Chalcogenides. Issue 32 (August 2015) - Han, Shi‐Kui; Gu, Chao; Gong, Ming; Yu, Shu‐Hong
Abstract The reaction of trialkylphosphines with a series of nanostructured chalcogenides results in metals and metal‐sulfide heterostructures.